Natural infection of murine norovirus in conventional and specific pathogen-free laboratory mice - Ohsugi, Takeo; Matsuura, Kumi; Kumar, Jerald M. (Frontiers in Microbiology, 2013)
Noroviruses cause most cases of acute viral gastroenteritis worldwide. The lack of a cell culture infection model for human norovirus necessitates the use of molecular methods and/or viral surrogate models amenable to cell culture to predict norovirus inactivation. Murine norovirus (MNV) may be used to construct a small animal model for studying the biology and pathogenesis of noroviruses because MNV is the only norovirus that replicates in cell culture and a small animal model. However, recent studies have shown that natural MNV infection is widespread in laboratory mouse colonies. We investigated MNV infection in both conventional and specific pathogen-free (SPF) genetically modified mice from Japan and the US, and commercial mice from several animal breeders in Japan, using serological and molecular techniques. MNV antibodies were detected in 67.3% of conventional mice and 39.1% of SPF mice from Japan and 62.5% of conventional mice from the US. MNV antibodies were also found in 20% of commercial SPF C57BL/6 mice from one of three breeders. Partial gene amplification of fecal isolates from infected animals showed that the isolates were homologous to reported MNV sequences. These results suggest that both conventional and SPF laboratory mice, including commercial mice, are widely infected with MNV, which might require considerable attention as an animal model of human disease.